POSTERIOR REVERSIBL ENCEPHALOPATHY SYNDROME IN COVID 19 DISEASE: A RARE CASE - Taşkın, Öztürk; Yılmaz, Ayşe; Soylu, Veysel Garani; Demir, Ufuk; Kurada, Gizem (Acil Tip Uzmanlari Dernegi, 2022)
Background: Covid-19 disease can have many neurological complications, posterior reversible encephalopathy being one of them. Case Report: A 42-year-old female patient was admitted to the emergency department on the 4th day of PCR test positivity with decreased consciousness. Patient with a Glasgow coma score of 6 (E1M3V2). The patient's vital signs were stable and there was no abnormality in his laboratory. No pathology was found in the brain tomography to explain the loss of consciousness. In MRI evaluation, the patient was diagnosed with Posterior reversible encephalopathy syndrome (PRES) according to radiological and clinical information. The standard Covid -19 treatment added to the antiedema treatment was applied to the patient. Brain MRI was repeated four days later and previous MRI findings showed regression. The patient was discharged to the ward with stable neurological status on the 22nd day of hospitalization. Conclusion: PRES is a rare but serious complication in Covid-19. Especially in the Covid-19 intensive care unit, intubation and sedation suppress the clinical picture, and the difficulty in getting patients on magnetic resonance imaging can complicate the diagnosis. Therefore, PRES should be kept in mind in the presence of neurological symptoms such as encephalitis, meningitis, encephalopathy and cerebrovascular disease.
Keywords: Klinik Tıp Bilimleri; Clinical Sciences; Covid-19; Posterior reversible encephalopathy syndrome; Intensive Care Unit; neurology; 3. Good health